Disparities in Utilization of Medical Specialists for Colonoscopy - Michele J. Josey; Cassie L. Odahowski; Whitney E. Zahnd; Mario Schootman; Jan M. Eberth (Mary Ann Liebert, 2019)
Purpose: Colonoscopy is the preferred screening modality for colorectal cancer (CRC) prevention. The quality of the procedure varies although medical specialists such as gastroenterologists and colorectal surgeons tend to have better outcomes. We aimed to determine whether there are demographic and clinical differences between those who received a colonoscopy from a specialist versus those who received a colonoscopy from a nonspecialist. Methods: Using the population-based South Carolina Outpatient Ambulatory Surgery Database, we looked retrospectively to obtain patient-level endoscopy records from 2010 to 2014. We used multilevel logistic regression to model whether patients saw a specialist for their colonoscopy. The primary variables were patient race and insurance type, and an interaction by rurality was tested. Results: Of the 392,285 patients included in the analysis, 81% saw a specialist for their colonoscopy. County of residence explained 30% of the variability in the outcome. Non-Hispanic black (OR=0.65; confidence interval [95% CI]: 0.64?0.67) and Hispanic patients (OR=0.75; 95% CI: 0.67?0.84) were significantly less likely than non-Hispanic white patients to see a specialist. Compared with commercial/HMO insurance, all other types were less likely to see a specialist, and even more so for rural patients. The interaction of race by rurality was not significant. Conclusions: Specialists play a key role in CRC screening and can affect later downstream outcomes. This study has shown that ethnic minorities and adults with public or other insurance, particularly in rural areas, are most likely not to see a specialist. These results are consistent with disparities in CRC incidence, mortality, and survival.